Auditory and non-auditory health effects of noise exposure among people working near traffic junctions in Mysuru city, Karnataka - D., Sunil Kumar; Thomas, Jose Jom; B., Prakash; M. R., Narayana Murthy; Chakrashali, Sulochanadevi B. (International Journal Of Community Medicine And Public Health, 2020)
Background: To assess the prevalence of health effects of noise exposure and the factors associated with it among people occupationally exposed to traffic noise in Mysuru city in Karnataka. Methods: A community based crossectional study was conducted for two months in Mysuru city in Karnataka. The sample size was calculated to be 280 and study participants were recruited from 70 selected locations in the city including all major traffic junctions with signal or traffic police control, covering all regions in the city. Four samples were assessed from each location by history taking and the ambient sound level was recorded from each location using a sound level meter. Data were entered in microsoft excel and analysed using SPSS version 22. Results: The prevalence of hearing loss among the study participants was 5.7% and 1.8% of people complained of tinnitus. Among the study participants, 8.9% had hypertension, 1.1% had cardiovascular disorders, 8.2% had sleeplessness, 6.4% had anxiety, 2.9% had irritability, and 5.7% reported a reduction working efficiency. The proportion of study participants with at least one health effect noise exposure was 26.07%. Only age group was significantly associated with the development of health effects among the exposed individuals. Conclusions: An alarming proportion of people working near traffic areas in Mysuru city are exposed to higher levels of noise and more than 25% of them show symptoms of auditory and/ or non-auditory health effects of noise pollution.